2018
DOI: 10.5505/bsbd.2018.60251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Studies in Turkey on the Prevention of Pressure Sores In the Intensive Care Unit: A Systematic Review

Abstract: bsbd@balikesir.edu.tr www.bau-sbdergisi.com ÖZET Son yıllarda giderek önem kazanan, yataklı tedavi kurumlarının hizmet kalite göstergesi olarak gösterilmeye başlayan basınç yarası kişinin yaşam kalitesini etkileyen, sağlık bakım hizmetlerinin maliyetini artmasına neden olan önlenebilir bir problem olarak karşımıza çıkmaktadır. Bu nedenle basınç yarasına neden olabilecek risk faktörlerinin belirlenmesi ve önlenmesi önemlidir. Basınç yarasının görülme sıklığı ve önlenmesine ilişkin yurt dışında çok sayıda çalışm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Development of pressure ulcer represents the inadequacy in nursing care quality and development of stage III or IV pressure ulcer is considered as a "never intolerable" event. [10] In a study that was performed in India, a high incidence was reported for stage 3 pressure ulcers on sacrum and heel [19] ; and in a study performed in Portugal, a high prevalence of stage 1 pressure ulcer was reported on sacrum and coccyx. [20] In this study, it was observed that stage 1 pressure ulcers that were seen at second week of mechanical ventilation treatment showed a bad course towards stage 2.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Development of pressure ulcer represents the inadequacy in nursing care quality and development of stage III or IV pressure ulcer is considered as a "never intolerable" event. [10] In a study that was performed in India, a high incidence was reported for stage 3 pressure ulcers on sacrum and heel [19] ; and in a study performed in Portugal, a high prevalence of stage 1 pressure ulcer was reported on sacrum and coccyx. [20] In this study, it was observed that stage 1 pressure ulcers that were seen at second week of mechanical ventilation treatment showed a bad course towards stage 2.…”
Section: Discussionmentioning
confidence: 97%
“…[7] According to the results of a systematic review including the studies performed in Turkey, it was revealed that nurses performed a limited number of interventions to prevent pressure ulcers, clinical decisions were insufficient and the follow ups were not conducted. [10] Yet, nurses can use their independent roles more efficiently and they can contribute to the reduction of hospitalization time, increase in the life quality of the patient and avoidance of economic losses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basınç yarasının önlenmesinde, yaraların gelişmesine neden olan etkenlerin belirlenmesi, etkenlere yönelik hemşirelik girişimlerinin planlanması ve uygulanması gerekmektedir. Basınç yaralarına yönelik eğitim almış yara bakım hemşireleri olmak üzere tüm hemşireler basınç yaraların önlenmesi ve bakımından sorumludur (34). Ameliyathane Kaynaklı Basınç Yaralarının Değerlendirilmesi Ameliyathane kaynaklı basınç yaralarını önlemede asıl amaç doku bütünlüğünün korunup devamlılığının sağlanmasıdır.…”
Section: Ameliyathane Kaynaklı Basınç Yaralarının öNlenmesi Ve Hemşirenin Rolüunclassified